Pemberdayaan Masyarakat melalui Pemanfaatan Daun Salam untuk Menurunkan Kadar Kolesterol secara Alami - Rindayani, Mila Febrina; Tanjung, Wilda Nurfadila; Yusri, Imelda (Jurnal Masyarakat Indonesia (Jumas), 2025)
Bay leaves (Syzygium polyanthum) are a herb widely used in Indonesian cuisine as a natural flavoring. However, beyond their culinary uses, bay leaves are also known to have various health benefits, one of which is helping to naturally lower cholesterol levels. Infusion is a preparation often used as a traditional medicine by the community and is very easy to consume in the form of herbal tea. Infusion also serves to enhance the taste and determine the characteristics of the herbal infusion. The purpose of this counseling is to determine the results of observations of cholesterol levels in hypercholesterolemic patients after being given bay leaf infusion. To determine the difference in changes in cholesterol levels in hypercholesterolemic patients before and after being given bay leaf infusion. To determine the effectiveness of bay leaf infusion in hypercholesterolemic patients. This counseling uses a lecture method by making a brew with the addition of the active ingredient from bay leaves. ar 200 mg/dL.